M185. THE EFFECTS OF GROUP ARTS THERAPY BASED ON EMOTION MANAGEMENT TRAINING ON THE EMOTIONAL EXPRESSION, ALEXITHYMIA, DEPRESSION AND QUALITY OF LIFE IN PATIENTS WITH SCHIZOPHRENIA. (18th May 2020) - Lim, Eunsung; Park, Sung-Yong; Jang, Seung-Ho; Bahk, Won-Myong; Kwon, Young-Joon; Yoon, Bo-Hyun; Lee, Kwanghun; Lee, Sang-Yeol
Abstract: Background: The objective of this study was to investigate the effects of group arts therapy based on emotion management training on emotional expression, positive emotion and negative emotion, alexithymia, depression and quality of life in patients with schizophrenia. Methods: 24 of 160 in-patients with schizophrenia, according to DSM-IV from H Mental Health Hospital, were randomly assigned to either an experimental or control group. Each group were consisting of 12 patients. Group arts therapy was conducted on the experimental group twice a week, 60 minutes per session, for a total of 16 sessions, while the control group was left untreated. The following scales were used for assessment: Berkeley Expressivity Questionnaire (BEQ), Positive Affective and Negative Affect Schedule (PANAS), Toronto Alexithymia Scale-Korean vesion (TAS-20K), Depression Scale for Schizophrenia (K-CDSS), Positive and Negative Syndrome Scale (PANSS), and Schizophrenia Quality of Life Scale (SQLS-R4K). Independent t-test was conducted to confirm the homogeneity, and to find the effects of group arts therapy, Repeated measures ANOVA was conducted to confirm the differences for scores of each scales regarding groups, measuring timing, and also the interaction between groups and measuring timing by pre, post and follow-up test. Results: The result of this study are as follows. First, total score, expressivity factors and impulse strength factors of emotional expressivity were significantly increased after group arts therapy compared to the control group. Second, positive emotion was significantly increased and negative emotion was significantly decreased after group integrative therapy compared to the control group. Third, total score, difficulty identifying feelings of Alexithymia were significantly decreased after group arts therapy compared to the control group. Fourth, depression was significantly decreased after group integrative arts therapy compared to the control group. Fifth, negative syndromes and general psychopathology were significantly decreased after group arts therapy compared to the control group. Sixth, quality of life was significantly increased after group arts therapy compared to the control group. Discussion: The group arts therapy have significantly improved the emotional expression, positive emotion, negative emotion and Alexithymia in patients with schizophrenia and also improved negative syndromes, general psychopathology, depression and quality of life. These result suggest that group arts therapy based on emotion management training could be a useful intervention for emotional disturbance treatment for in patients with schizophrenia.